2015 IEEE International Conference on Communication Workshop (ICCW) 2015
DOI: 10.1109/iccw.2015.7247551
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Infotainment and Safety Application for VANET dissemination

Abstract: Vehicular Ad-hoc NETworks (VANETs) are rapidly\ud increasing their popularity and ductility, being an essential\ud element for smart cities and smart driving. Layer three standards\ud have already been approved, but they do not pursue optimality\ud in terms of high throughput. This paper aims to identify a new\ud algorithm to put on top of the standard routing layer, namely\ud Self hEaling Infotainment and safetY Application (SEIYA), in\ud order to create a vehicular distributed backbone, able to stay up\ud as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To address this problem, a secure performance‐enhanced channel‐allocation security model based on the commutative RSA (Rivest–Shamir–Adleman) system is proposed in [21]. In [22], cell‐based data transactions in intelligent transportation systems are analyzed emphasizing path setup delay and time overhead. The uniqueness of transportation networks demands the deployment of specific security methods to address problems with vehicle‐to‐everything communication.…”
Section: Related Workmentioning
confidence: 99%
“…To address this problem, a secure performance‐enhanced channel‐allocation security model based on the commutative RSA (Rivest–Shamir–Adleman) system is proposed in [21]. In [22], cell‐based data transactions in intelligent transportation systems are analyzed emphasizing path setup delay and time overhead. The uniqueness of transportation networks demands the deployment of specific security methods to address problems with vehicle‐to‐everything communication.…”
Section: Related Workmentioning
confidence: 99%
“…Das et al [23] have developed a prototype for infotainment system for gesture identification is carried out in involuntary manner. The work of Felice et al [24] has presented a design of the infotainment system that uses self-healing mechanism in order to support critical application. Chen et al [25] have used television spectrum bands for relaying services over infotainment system.…”
Section: Related Workmentioning
confidence: 99%
“…Previous research have shown that VANETs suffers from several challenges; which need to be highlighted, due to the possibility of increasing number of connected devices in the system, resources utilization, unbalanced traffic flow, geographical circumstances, unreliable network connectivity and broadcast storm [1], [19], [26]. However, this paper aims to address the issues of routing protocols and security and privacy in VANETs.…”
Section: Vanets Challengesmentioning
confidence: 99%